State Information Capacity as Information Sovereignty Basis - Igor F. Kefeli; Sergey A. Malmberg (Управленческое консультирование)
This article examines the confrontation of states in the information space and aspects of the state information policy in terms of protecting information sovereignty. The purpose of this study is to introduce the concept of “information capacity of the state” and justify the need for its use in planning and organizing internal and external policy management activities to protect the information sovereignty of the state. On the basis of research, using the methods of comparative and situational analyzes, a common factor has been identified. This factor determines capabilities of states in the information space, it is “information capacity of the state”. The essence of the concept of “information capacity of the state” is defined and it was demonstrated that the information capacity of the state is the basis of information sovereignty. The analysis of domestic and foreign experience of applying the information capac ity of the state in the conduct of information policy in order to protect information sovereignty was done. The steps to ensure compliance with the legislation of the Russian Federation on the example of blocking access to the Telegram messenger from the territory of the Russian Federation were analyzed. As a result of this analysis, it was concluded that it is impossible to ensure the legislation of the Russian Federation in the information space using the current information capacity of the state. To solve this problem, the article proposes to use not only technical, but also organizational measures. To prevent this situation from recurring in future, it is proposed to introduce the concept of “information capacity of the state”, defined in this article, into the regulatory acts governing the state information policy (National Security Strategy of the Russian Federation, Doctrine of Information Security of the Russian Federation, Federal Law № 149-ФЗ).